The Use of Fractional Card Media-Based Concept Attainment Models to Improve Understanding of Fractional Concepts - Ramadhanti, Auliya; Simamora, Nadia Natalia (Journal of Basic Education Research, 2023)
Purpose of the study: To find out the application of the Concept Attainment model with the help of fractional card media in increasing understanding of the concept of fractions in class II Ahmad Dahlan Elementary School. Methodology: The research was conducted at Ahmad Dahlan Elementary School in the even semester of 2018/2019. The research sample was 22 students. Research data obtained through student learning outcomes and observation sheets. Quantitative data were analyzed using descriptive statistics and Qualitative data were analyzed to determine the learning process using the Concept Attainment learning model based on fractional card media. Main Findings: The results of the study show that the application of the Concept Attainment model assisted by fractional card media can improve understanding of the concept of fractions. By observing the results of understanding the concept of fractions in the first cycle, namely 53.01%, it increased in cycle II to 77.12%. In cycle I the results of the written test evaluation with classical completeness of 63.15% increased in cycle II by 18.66% to 81.81%. Novelty/Originality of this study: The latest research in this research is to combine the concept learning learning model with fraction card media which is generally not widely used, especially for learning fractions in elementary school mathematics, the benefits for students in this action research will then make it easier for them to face more difficult learning levels in the next class and can become a new teaching idea for teachers to facilitate student understanding.